Neutropenia and agranulocytosis in England and Wales: incidence and risk factors. - van Staa, T; Boulton, F; Cooper, C; Hagenbeek, A; Inskip, H; Leufkens, H (2003)
The objectives of this study were to estimate the incidence of idiosyncratic neutropenia and agranulocytosis in England and Wales and to evaluate their risk factors and outcomes. The study was conducted using data from the General Practice Research Database. All cases of idiosyncratic neutropenia or agranulocytosis were identified and the incidence was estimated. This was followed by a nested case-control study, estimating odds ratios with drug exposure from conditional logistic regression. From 1987 to 1999, 3,224 patients with idiosyncratic neutropenia (50 with agranulocytosis) were identified. The incidences of neutropenia and agranulocytosis were estimated to be 120 and 7 cases per million people per year, respectively. The adjusted odds ratios for neutropenia were 34.7 (95% confidence interval 12.0-99.7) for current users of thyroid inhibitors, 9.5 (4.4-20.8) for users of disease-modifying antirheumatic drugs, and 7.6 (4.9-11.9) for users of aminosalicylates. Other drugs with statistically significantly increased risks of neutropenia included antibacterial drugs, non-opioid analgesics, NSAIDs, antidepressants, ulcer-healing drugs, and anti-epileptics. The increase in risk of neutropenia predominantly occurred during the first months of treatment. For most drugs investigated in this study, there was no relationship to daily dose. The excess 1-year mortality was low among neutropenia and agranulocytosis cases and mostly explained by the underlying disease state. In conclusion, the highest risks of neutropenia were generally found in patients starting treatment. The excess 1-year mortality was low among neutropenia and agranulocytosis cases and can be mostly explained by the underlying disease state.